Partisipasi Masyarakat dalam Program Pemberdayaan Kesejahteraan Keluarga di Kelurahan Wandoka Kabupaten Wakatobi - Setianingsi, Eka; Nastia, Nastia; Basir, Muh. Askal (Journal of Government Science Studies, 2022)
This study aims to determine the participation of women in the Family Welfare Empowerment Program in North Wandoka Village, Wangi-Wangi District, Wakatobi Regency. This research uses descriptive research with a quantitative approach, which is a research method used to examine the condition of natural objects, so the researcher is the key instrument. The findings show that community involvement in the primary PKK program went quite well, because of the community's knowledge to participate through involvement in events carried out by the PKK driving team in North Wandoka Village. Furthermore, community involvement in the main PKK program can be considered as community self-help, both in terms of manpower and supplies. The problem in North Wandoka Village is the lack of public education. It is recommended that the involvement of the North Wandoka Village community in the PKK program be increased again, and the PKK mobilizing team as the executor of tasks in North Wandoka Village to maximize community involvement in various activities.